PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA BERBANTUAN APLIKASI FLIPHTML5 - Siti Syahirani; Nur Rahmi Rizqi; Khoiruddin Matondang (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This research aims to investigate the effect of the Problem-Based Learning (PBL) learning model on the mathematical communication skills of class XI MAS students at the UNIVA Medan Project, with the help of the FlipHTML5 application. The method used in this research is quasi-experimental with a factorial design. Data collection was carried out through mathematical communication skills tests and statistical analysis to test hypotheses. The results showed that there was a significant increase in the mathematical communication skills of students in the experimental group compared to the control group. The average posttest score for the experimental group was 85.52, while the control group was 78.04. It is indicated that this difference did not occur by chance, but rather was the result of differences in the treatment applied. In addition, the FlipHTML5 application was proven to be effective in improving students' mathematical communication skills with an average score percentage of 73.63% in the experimental class compared to 71.37% in the control class. These results indicate that the use of the FlipHTML5 application in learning with the PBL model makes a positive contribution to improving students' mathematical communication skills.